(untitled) (Journal of Pakistan Orthopaedic Association, 2014)
Background: Surgical Site Infection (SSI) is one of the common and increases patient morbidity, hospital stay and treatment cost. Objective: To determine the risk of SSI with and without the use of closed suction drain in clean hip. Material & Methods: This randomised controlled trial of 314 patients was carried out from May 2012 to April 2013, were randomly allocated into two groups â€œAâ€ and â€œBâ€. In-group â€œAâ€ operated with closed suction drain placed at surgical site while group â€œBâ€ operated without placement of a closed suction drain. Patients followed on 2nd, 7th, 14th and 30th postoperative days to look for any signs of infection like redness, discharge of pus or collection. Results: Among 314 patients, total 7(2.2%) patients developed surgical site infection, 4 patients (2.5%) in group A and 3(1.9%) in group B. Age of patients in group A range from 4 to 90 while in group B the age ranged from 5 to 90 years. In-group A 110(70.1%) male, 47(29.9%) were female. Male to female ratio was 2.34:1. While in-group B 100(63.7%) male and 57(36.3%) were female. Male to female ratio was 1.75:1. One patient in each group (0.63%) developed SSI and it was superficial on 2nd postoperative day. Four patients, 2 in each group presented with SSI on 7th postoperative day. One patient in-group â€œAâ€ developed SSI on 30th postoperative day. Conclusion: There is statistically no significant difference in the rate of SSI whether a closed suction drain is placed or not placed in clean hip surgery. Key words: Surgical site infection, Closed suction drains, Hip surgery